Descending aortic replacement after Nuss for pectus excavatum in a Marfan patient—Case report. (2016) - Jaroszewski, Dawn; Ewais, MennatAllah; DeValeria, Patrick; Gotway, Michael; Craig Miller, D.
Highlights: The Nuss procedure for pectus excavatum repair has been successfully performed in Marfan patients. There is concern for future risk of aortic dilation/rupture and need for emergent access with the support bars in place. Successful descending aortic replacement can be performed with the Nuss bars in places. Abstract: Introduction: The Nuss procedure for pectus excavatum (PE) repair has been successfully performed in Marfan syndrome (MFS) patients however there is concern for future risk of aortic dilation/rupture and need for emergent access with support bars in place. Case presentation: We present a 45 year-old male with MFS that required descending aortic replacement shortly after modified Nuss repair. Discussion: The majority of MFS patients have severe PE and repair with the Nuss procedure is not uncommon. The risk for life threatening aortic dilation, dissection, or rupture in such patients is a concern when utilizing this technique. Our work has been reported in line with the CARE criteria. Conclusion: Nuss repair should be considered in MFS patients with technique modifications and careful consideration of future risk of aortic dilation and rupture.